2021
DOI: 10.3892/etm.2021.10307
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits the viability, migration and invasion of papillary thyroid cancer cells by regulating the miR‑301a‑3p/STAT3 axis

Abstract: Thyroid cancer is one of the most common malignant tumors, and the mortality rate associated with thyroid cancer has been increasing annually. Curcumin has been reported to exert an antitumor effect on papillary thyroid cancer (PTC), and the identification of additional mechanisms underlying the anticancer effect of curcumin on PTC requires further investigation. The present study aimed to explore the effects of curcumin on the viability, migration and invasion of PTC cells. TPC-1 cells were incubated with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The potential mechanisms might be attenuating lncRNA H19 [ 29 ]. Another study suggested that the migration and invasion of papillary thyroid cancer TPC-1 and BCPAP-R cells were suppressed by curcumin through up-regulation of miR-301a-3p [ 78 ]. Furthermore, curcumin significantly inhibited wound closure and invasion of pancreatic cancer Patu8988 and Panc-1 cells, which was mediated by inhibiting neural precursor cell expressed developmentally down-regulated protein 4 (NEDD4)/Akt/mTOR pathway [ 90 ].…”
Section: Effects and Mechanisms Of Curcumin On Cancersmentioning
confidence: 99%
“…The potential mechanisms might be attenuating lncRNA H19 [ 29 ]. Another study suggested that the migration and invasion of papillary thyroid cancer TPC-1 and BCPAP-R cells were suppressed by curcumin through up-regulation of miR-301a-3p [ 78 ]. Furthermore, curcumin significantly inhibited wound closure and invasion of pancreatic cancer Patu8988 and Panc-1 cells, which was mediated by inhibiting neural precursor cell expressed developmentally down-regulated protein 4 (NEDD4)/Akt/mTOR pathway [ 90 ].…”
Section: Effects and Mechanisms Of Curcumin On Cancersmentioning
confidence: 99%
“…STAT3 is pivotal in regulating the progression, metastasis, and immune evasion of TNBC ( Qin et al, 2019 ). In fact, CUR has been reported to suppress the proliferation, migration, and invasion of cancer cells by suppressing STAT3 activity ( Datta et al, 2018 ; Liang et al, 2021 ). AKT1 increases the proliferation and survival of cancer cells and AKT inhibitors could control the progression, drug resistance, and immunosuppression of breast cancer ( Hinz and Jücker, 2019 ; Jabbarzadeh Kaboli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that curcumin may affect the EMT process and MMPs secretion through miRNA- and lncRNA-mediated mechanisms. For example, curcumin may inhibit the expression of JAK/STAT signaling effector proteins p-JAK1, JAK1, p-JAK2, JAK2, p-JAK3, JAK3, p-STAT1, STAT1, p-STAT2 and STAT2 by upregulating miR-301a-3p, thus affecting the vitality of thyroid cancer cells TPC-1 [ 48 ]. Cai et al [ 49 ] found that lncRNA H19 can activate the EMT process, as well as invasion and metastasis of breast cancer MCF 7/TAMR cells, whereas curcumin can reverse these phenotypes induced by lncRNA H19.…”
Section: Curcumin In Treatment Of Malignant Tumorsmentioning
confidence: 99%